FAKTOR DETERMINAN RISIKO KURANG ENERGI KRONIS (KEK) PADA IBU MENYUSUI DI INDONESIA - Anies Irawati (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2009)
ABSTRACT Mid-upper arm circumference (MUAC) is a indicator to screen the risk of chronic energy deficiency of lactating women. In developing countries, it is used to select lactating women for nutrition intervention. In Indonesia, there is a few studies to examine risk factors associated with chronic energy deficiency of lactating women (MUAC < 23.5 cm). Using data Riskesdas (Baseline Health Research) 2007, will determine breastfeeding pattern, mother activity and morbidity, demography factors and family energi consumption associated with the risk of chronic energy deficiency. The subject was lactating women who still breastfed the children under 2 years old. A total 22076 subject were used for the analysis using logistic regression analysis. The result showed that the prevalence the risk of chronic energy deficiency among lactating women in Indonesia was 34.6%. The risk of chronic energy deficiency lactating women to infant 0–5 months is associated between predominantly breasfeeding controlling by parity, and protein consumption < 80% AKG. The risk of chronic energy deficiency lactating women to children 6-23 months is associated between breastfeeding pattern controlling by parity, protein consumption < 80% RDA, heavy activity and ISPA. . [Penel Gizi Makan 2009, 32(2): 82-93] Keywords: lactating woman, mid-upper arm circumference (MUAC), chronic energy deficiency, breastfeeding pattern